Fuzzy logics and medical diagnosis of nursing assessment (Bangladesh Journal of Scientific and Industrial Research, 2015)
This paper argues that fuzzy representations are appropriate in applications where there are major sources of imprecision and / or uncertainty. Case studies of fuzzy approaches to specific problems of medical diagnosis and classification are described in support of this argument. The solutions use a variety of fuzzy methods including clustering, fuzzy set aggregation and type- 2 fuzzy set and Type-2 fuzzy relation modeling of linguistic approximations. It is concluded that the fuzzy approach to the development of artificial intelligence in application systems is beneficial in these contexts because of the need to focus on uncertainty as a main issue. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22631 Bangladesh J. Sci. Ind. Res. 49(4), 271-274, 2014